2009
DOI: 10.1055/s-0028-1105931
|View full text |Cite
|
Sign up to set email alerts
|

Genotype Distributions in Top-level Soccer Players: A Role forACE?

Abstract: We determined the genotype and allelic frequency of several genetic polymorphisms (ACE I/D, GDF-8K153R [and also E164K, P198A and I225T] and AMPD1 C34T) that are candidates to influence sports performance in a group of 54 male professional soccer players. Their results were compared with those of elite endurance male athletes (52 runners) and 123 sedentary, healthy men (controls). We found statistical significance for the ACE ID (chi (2)((2))=8.176, P=0.017) and II genotypes (chi(2)((2))=16.137, P<0.001) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 32 publications
2
41
1
2
Order By: Relevance
“…The resulting PCR products were genotyped by single base extension (SBE) (Juffer et al 2009). The primers used for A55T, E164K, I225T K153R and P198A were 5′CTAAATCTTCAAGAATAGAA-3′, 5′-CAAACACTGTTGTAGGAGTCT-3′, 5′-CTG AATCCAACTTAGGCA-3′, 5′-TTTAATACAATA CAATAAAGTAGTAA-3′, and 5′-TTTTTTTT ATCTCTGAAACTTGACATGAAC-3′, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting PCR products were genotyped by single base extension (SBE) (Juffer et al 2009). The primers used for A55T, E164K, I225T K153R and P198A were 5′CTAAATCTTCAAGAATAGAA-3′, 5′-CAAACACTGTTGTAGGAGTCT-3′, 5′-CTG AATCCAACTTAGGCA-3′, 5′-TTTAATACAATA CAATAAAGTAGTAA-3′, and 5′-TTTTTTTT ATCTCTGAAACTTGACATGAAC-3′, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Two recent studies showed a higher proportion of the R allele of the R577X polymorphism in the α-actinin-3 (ACTN3 ) gene, and of the DD genotype of the Insertion(I)/Deletion(D) polymorphism in the angiotensin-converting enzyme (ACE) gene, in world-class professional soccer players compared with non-athletic controls and elite endurance athletes [12,23]. In addition, Fatini et al showed that the ACE D allele is associated with training-induced changes in the left ventricular mass of elite Italian soccer players [7].…”
Section: Introductionmentioning
confidence: 99%
“…; 54 profesyonel erkek futbolcu; 52 elit erkek koşucu ve 123 sağlıklı erkek kontrol gruplarında yaptıkları çalış-mada, 52 elit erkek koşucuda, ADE II ve ADE I/D genotipinin kontrol grubuna göre istatistiksel olarak daha anlamlı olduğunu, fakat futbolcularda bu polimorfizm açısından fark bulunmadığını belirlemişlerdir. 43 ADE DD genotipli kişilerin maxVO 2 gerektiren kısa süreli aerobik dayanıklılık sporlarında daha iyi performansa ve dolayısıyla daha yüksek maxVO 2 düzeyine sahip olduğu saptanmıştır. 44,42 Rankinen ve ark., beyaz (476) ve siyah (248) ırktan oluşan büyük heterojen grubun içinde yer alan beyaz ebeveynlerden, ADE DD genotipine sahip olanların antrenmanlara daha yüksek maxVO 2 artışı ile yanıt verdiğini saptamışlardır.…”
Section: Anji̇yotensi̇n I-dönüştürücü Enzi̇m Geni̇unclassified